A novel service scheduling policy based on logical subnet partitioning in Bio-Grid environments. (8th June 2011) - Jiang, Wenchao; Zhou, Yanhong; Jin, Hai; Baumgarten, Matthias
In this paper, we present a method called SP2SP, 2-level Grid Service Scheduling Policy based on Logical Subnet Partitioning (LSP), which tackles the service scheduling problem in Bio-Grid environments through three steps: (a) a similarity-based logical subnet partitioning algorithm which classifies individual services into different subsets according to similarity constraints that are based on performance metrics; (b) the employment of a requirement-based prediction algorithm that maps the bioinformatics applications that are composed of multiple sub-tasks into optimal subnet and (c) multi-priority queue-based service scheduling algorithm used inside individual subnet taking charge of allocating each sub-task to an optimal physical service within the subnet. Based on the sub-grid platform of NPPC, experimental results have shown that SP2SP outperforms other scheduling algorithms. In particular, SP2SP performs best for scenarios where a group of tasks has similar resource requirements or need to cooperate with each other to obtain better performance as a whole.